BSMI’s Medical Humanitarian Mission in Gaza: A Study on Global Health Outreach and Community Impact - Satiadharmanto, Deddi Fasmadhy; Nugraha, Nurcholis Hendry; Supartono, Basuki (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The second Emergency Medical Team (EMT) mission of the Indonesian Red Crescent (BSMI) to Gaza aimed to deliver direct healthcare services and medical knowledge transfer during armed conflict. A multidisciplinary team (4 specialist physicians and 1 dentist) implemented an integrative service-learning approach over 16 days (17 April – 2 May 2025) at Al Nasser Hospital, Khan Younis, through three strategies: (1) emergency medical services, (2) resident/intern education mentoring, and (3) stem cell therapy for wound care. The team managed 287 emergency cases (42% fractures, 28% deliveries, 30% infections) and trained 23 local medical staff. Key challenges included medical equipment shortages (67% unmet needs) and security instability. The service-learning collaboration effectively enhanced crisis response capacity. Urgent recommendations include: opening humanitarian corridors, sustaining team rotations, and advancing medical diplomacy.